Pengaruh Covid-19 Atas Berlakunya Regulasi Proses Perizinan Usaha Pertambangan Melalui Sistem Online Single Submission Berbasis Risiko: The Effect of Covid-19 on the Enactment of Regulations on the Mining Business Licensing Process Through a Risk-Based Online Single Submission System - Rahayu, Sang Ayu Putu (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Regulatory developments in Indonesia are still rolling, including in the investment sector. Indonesia now enforces a licensing system using electronic media called the Online Single Submission Risk-Based Approach (referred to as OSS-RBA). This system applies to the business sector in Indonesia, including the mining investment sector. This sector has a relatively high risk, so it is essential to understand the implementation of risk-based business licensing in this mining investment sector. In addition, the enactment of risk-based OSS occurred during the covid-19 pandemic, which still affects business activities in Indonesia. In the end, this article aims to find out the effect of covid-19 on changes in business license regulations with OSS-RBA in the mining sector. In the future, the presence of OSS-RBA, which is now mandatory for use by investors, including in the mining sector, on the one hand, will facilitate the process, especially during the pandemic. The use of electronic systems will help to break the chain of the spread of the covid-19 virus. However, on the other hand, pandemic conditions will still be difficult because it turns out that socialization is still essential. System adjustments and direct communication are still needed between investors and the government. However, there are online media to help communication-related to the difficulties caused by the implementation process. The condition of the covid-19 pandemic is a starting point for momentum to utilize electronic systems in the licensing process in Indonesia to accelerate the business climate in Indonesia.